Cancer stem cell signaling pathways. (September 2016) - Matsui, William H.
Abstract : Abstract: Tissue development and homeostasis are governed by the actions of stem cells. Multipotent cells are capable of self-renewal during the course of one's lifetime. The accurate and appropriate regulation of stem cell functions is absolutely critical for normal biological activity. Several key developmental or signaling pathways have been shown to play essential roles in this regulatory capacity. Specifically, the Janus-activated kinase/signal transducer and activator of transcription, Hedgehog, Wnt, Notch, phosphatidylinositol 3-kinase/phosphatase and tensin homolog, and nuclear factor-κB signaling pathways have all been shown experimentally to mediate various stem cell properties, such as self-renewal, cell fate decisions, survival, proliferation, and differentiation. Unsurprisingly, many of these crucial signaling pathways are dysregulated in cancer. Growing evidence suggests that overactive or abnormal signaling within and among these pathways may contribute to the survival of cancer stem cells (CSCs). CSCs are a relatively rare population of cancer cells capable of self-renewal, differentiation, and generation of serially transplantable heterogeneous tumors of several types of cancer.